2020
DOI: 10.9778/cmajo.20190195
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes during pregnancy and perinatal outcomes among First Nations women in Ontario, 2002/03–2014/15: a population-based cohort study

Abstract: iabetes mellitus during pregnancy, either preexisting diabetes or gestational diabetes, is a major contributor of adverse outcomes. In Canada, the number of women affected by diabetes during pregnancy has increased over time, 1,2 and the risk is higher in First Nations women. 3-6 Although Ontario is home to the largest group of First Nations people in Canada (23.6%), 7 little is known about the health care experience of pregnant First Nations women in the province. There are complex social and historical facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Suboptimal glycemic control around conception increases the risks of congenital malformations, spontaneous abortion, and fetal death 28,127,129–137 . A planned pregnancy in a person with diabetes in optimal glycemic control and good health carries only slightly higher risks than those in the general population but not as elevated as previously reported in those with suboptimal glycemic control.…”
Section: Sexual Healthmentioning
confidence: 96%
“…Suboptimal glycemic control around conception increases the risks of congenital malformations, spontaneous abortion, and fetal death 28,127,129–137 . A planned pregnancy in a person with diabetes in optimal glycemic control and good health carries only slightly higher risks than those in the general population but not as elevated as previously reported in those with suboptimal glycemic control.…”
Section: Sexual Healthmentioning
confidence: 96%
“…It was observed that these adverse perinatal outcomes were more commonly seen in a hospital serving the Aboriginal people in Northwest Ontario [12]. A study by Vélez et al, published in 2020, provides data showing that the Aboriginal communities also have the burden of undiagnosed type 2 diabetes in women of reproductive age that becomes apparent only during their first prenatal visit to the obstetrician [13].…”
Section: Disparities In Age and Gendermentioning
confidence: 99%
“…There are many programs for financial aid for indigenous communities, but even with these, there are other barriers to accessing healthcare such as their geographic location and transportation facilities, especially during Canadian harsh winters [26]. Even though the number of visits to a primary care physician was adequate, access to specialized care was limited [13]. Diabetes is a complex disease affecting many parts of the body, and specialists such as endocrinologists, ophthalmologists, and podiatrists are needed for the adequate management of diabetes.…”
Section: Challenges In Management Of Diabetesmentioning
confidence: 99%
“…More recent estimates suggest that in high-income countries, pre-existing diabetes occurs in seven to 15 per 1000 pregnancies [ 12 , 13 ]. A population-based cohort study in Ontario, Canada found the rate of pre-existing diabetes in pregnancy significantly increased in non-Indigenous women from 13.9 to 20.5 per 1000 deliveries from 2002 to 2015 ( p < 0.001), while the rates for Indigenous women were 40.5 per 1000 deliveries in 2015 [ 14 ]. Considerations for this increasing and changing demographic include less frequent exposure to preconception planning and a shorter duration of the condition in women with T2D [ 15 ], which may lead to less preparedness for the intense self-management requirements of pregnancy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%